Petrogenesis and tectonic setting of Mid‐Triassic volcanic rocks in the East Kunlun orogenic belt, NW China: Insights from geochemistry, zircon U–Pb dating, and Hf isotopes. (15th February 2021) - Tian, Nan; Sun, Fengyue; Pan, Zhongcui; Li, Liang; Yan, Jiaming; Wu, Dongqian; Gu, Yan; Deng, Jiafang; Liu, Zhedong; Wang, Li; Zhang, Yajing
Abstract : The Elashan magmatic belt is located at the eastern margin of the East Kunlun orogenic belt (E‐KOB) in northwestern China, where voluminous magmatism occurred during the Late Permian to Late Triassic. Mid‐Triassic volcanism produced the Xilikete Formation, which shows a geochemistry similar to that of highly fractionated I‐type (HFI) volcanic rocks. These rocks are characterized by high SiO2 (73.82–74.97 wt%), differentiation index (DI; 91.01–94.69), and alkalis (e.g., high K2 O + Na2 O, with K2 O/Na2 O ratios greater than 1.0) and by enrichment in some large‐ ion lithophile elements (LILEs; e.g., Rb, K, and Pb) and depletion in other LILEs (e.g., Ba and Sr) as well as some high‐field‐strength elements (HFSEs; e.g., Nb, Ta, and Ti); these features confirm that they are HFI volcanic rocks. Zircon U–Pb ages indicate that the volcanic rocks were emplaced at ~239 Ma. These zircons have εHf (t) values ranging from −2.26 to +0.36, with two‐stage model ages (TDM2 ) of 1, 441–1, 221 Ma, indicating a magma source that involved partial melting of Mesoproterozoic lower crust accompanied by a minor juvenile mantle component. The ~240 Ma magmatism in the E‐KOB was probably developed in response to subduction of the Palaeo‐Tethys oceanic plate. Previous studies indicate that a tectonic transformation from subduction to continental collision occurred at ~240 Ma. Combining these data with regional geological observations, we conclude that the Daheba volcanic rocks formed in an active continental margin setting related to the subduction of the Palaeo‐Tethys oceanic plate beneath the E‐KOB. Abstract : During the Early–Middle Triassic, the subducted Palaeo‐Tethys oceanic plate brought water from the surface to the lower mantle or even deeper, followed by water loss through dehydration reactions in the mantle transition zone. A wet mantle formed with enrichment by fluids or melts; it then rose due to its own buoyancy. A large quantity of high‐temperature magma from underplating caused upwelling of the asthenosphere and decompression of the lithosphere. These processes led to partial melting of the Mesoproterozoic lower crust, which produced magma with similar island arc geochemical characteristics. Subsequently, a deep magma chamber formed. Part of the primitive magma was emplaced and formed intermediate‐mafic intrusions (e.g., gabbro and diorite). Another part, extracted from this deep magma chamber, provided the necessary replenishment for the shallow magma chamber in the upper crust. At the same time, the magma experienced further fractionation in the shallow chamber, developing a high‐silica magma with characteristics of high fractionation. As the magma evolved, syenogranite and highly fractionated granite were emplaced. Therefore, we constructed a model of the mechanisms of Early–Middle Triassic granitic magmatism to represent the petrogenesis of highly fractionated I‐type volcanic rocks in the Daheba area.